TPD52L2 impacts proliferation, invasiveness and apoptosis of glioblastoma cells via modulation of wnt/β-catenin/snail signaling. (2nd November 2017) - Qiang, Zhou; Jun-jie, Li; Hai, Wang; Hong, Li; Bing-xi, Lei; Lei, Chen; Wei, Xiang; Ya-wei, Liu; Huang, Annie; Song-tao, Qi; Yun-tao, Lu
Abstract : We demonstrated TPD52L2 impacts proliferation, invasiveness and apoptosis of glioblastoma (GBM) cells and the prognosis of GBM patients received standard radiotherapy plus concomitant and adjuvant temozolomide (Stupp strategy) via modulation of Wnt/β-catenin/Snail signaling. Abstract: Intratumoral heterogeneity greatly hinders efficiency of target therapy in glioblastoma (GBM). To decipher the underlying mechanisms of heterogeneity, patient-derived adult GBM cells were separately isolated from margins of T1 gadolinium enhancing tumor lesions (PNCs) and T1 gadolinium enhancing core lesions (ECs). Single clone culture was conducted in ECs and U87MG cell line to screen clones with distinct biological phenotypes. Single cell clones with diverse phenotypes were simultaneously separated from ECs and U87 cell line. PNCs, GCs(H) and U87(H) exhibited longer cellular protrusion than ECs, GCs(L) and U87(L), respectively. Cell strains with longer protrusion exhibited higher invasive ability and lower sensitivity to temozolomide (TMZ) and radiation. Subsequently, TPD52L2 was verified as the functional protein to regulate the cellular heterogeneity by the proteomics analysis. Downregulation of TPD52L2 enhanced cell invasion whereas inhibited cell proliferation rate and sensitivity to chemotherapy in vivo and in vitro, this condition was reversed when TPD52L2 was overexpressed. The invasiveness was facilitated by up-regulating CTNNB1/β-catenin and SNAI1/Snail mediated EMT process. In addition, the clinical data of 88 GBM cases in our neurosurgery center was analyzed to reveal the influence of TPD52L2 in the prognosis of GBM. Low expression of TPD52L2 exacerbated prognosis of GBM patients received standard radiotherapy plus concomitant and adjuvant TMZ (Stupp strategy). Taken together, TPD52L2 is an important biomarker influencing GBM prognosis.